Continuous glucose monitoring to assess glycemic control in the first 6 weeks after pancreas transplantation. Issue 10 (11th October 2019) - Dadlani, Vikash; Kaur, Ravinder Jeet; Stegall, Mark; Xyda, Souzana‐Eirini; Kumari, Kanchan; Bonner, Keisha; Smith, Byron; Thapa, Prabin; Dean, Patrick G.; Kudva, Yogish C.
Abstract: Background: Current therapy for Type 1 diabetes (T1D) is characterized by significant glucose variability (GV). Pancreas transplantation (PT) is performed in certain T1D patients with and without end‐stage renal disease. To date, GV has been examined to a limited extent after PT. Methods: We investigated GV using continuous glucose monitoring (CGM) 3‐6 weeks after PT. Results: Eleven patients had simultaneous kidney pancreas transplantation (SPK), nine pancreas after kidney (PAK), and six pancreas transplantation alone (PTA). Mean CGM showed no difference between SPK, 126.5 ± 13.9, PAK 119.9 ± 12.8, and PTA 131.1 ± 29 mg/dL ( P value .6). Percentage of time in range (TIR, 70‐180 mg/dL) was 92% for SPK, 93.4% in PAK, and 88.5% in PTA with only 0.3%, 1.5%, and 0.3% of time <70 mg/dL. Percentage >180 mg/dL was 7.9% for SPK, 4.9% PAK, and 11% in PTA. Other measures of GV were similar in the three cohorts. In six patients, CGM was performed before and after PT and improved significantly. GV was also better compared with a matched cohort of T1D patients. Conclusions: All 3 types of PT resulted in excellent glucose control 3‐6 weeks post‐procedure. CGM outcomes represent an important objective outcome after PT.